REVIEW OF THE CONCEPT OF JU'ALAH ON INCOME EARNED FROM LIVE STREAMING ON SOCIAL MEDIA: A CASE STUDY ON TIKTOK APPLICATION - Al Hilal Akbar; Nurdin Bakri (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This research examines the concept of ju'alah in Islam and its application to income earned from live streaming activities on social media, focusing on the Tiktok application. Ju'alah is one of the contracts in fiqh muamalah, which is an agreement that promises certain rewards for parties who perform certain tasks. In the context of live streaming, the income received by streamers generally comes from audience gifts in the form of stickers which are then converted into money. The research method used in this study is a mixed methods research method that combines normative and empirical methods included in qualitative research. This research is descriptive in nature where most of the data used comes from interviews, observations in the form of sentences or narratives. The results of this study indicate that gifting is in accordance with the ju'alah contract if it is given after the implementation of the audience request. If there is fraud such as a gift has been given but the request has not been carried out in this case there is no positive legal action because there is no written agreement, while in Islam this is considered fraud so that the money earned by the creator is considered not halal.